A Novel Approach for Improving Profitability in the Construction Industry - HEIDAR, BASHIR HUSSAIN (İstanbul Kültür Üniversitesi, 2022)
With the increase in population and population density in cities, the construction industry has grown significantly. The number of towers and skyscrapers are increasing every day. The need for vertical transportation is one of the irreplaceable needs. Hence, many elevator companies have emerged. One of the main challenges for elevator companies is to compete with other companies in the industry. Establishing a company in the market, attracting customers to buy their products and elevators, serving customers, and developing the business and financial strength of elevator companies by having a proper plan in sales and marketing are the critical issues of managers and founders of companies. By analyzing the existing elevator companies and the needs of customers in this industry, company's management can find the weaknesses and strengths of the companies and based on it, adopt a better strategy to serve more customers in the market. This study provides a novel and useful method, named as Accompany Index Method (AIM) to develop in profitability in a firm. The novel and innovative method is implemented by examining the type of customer demands, project regions division, products and services type, and organizing other project details in different categories of attributes. The AIM method applied to the data of an elevator company located in Dubai, which will guide the management of this company to perform projects by considering elevator modernization and sales of the parts. In addition, the translation of the results shows that some of the attributes like "villa lifts", "maintenance" and "elevator repair" should not consider in AIM to filter the high profitable projects. Considering the dependent attributes and independent attributes at the same time is the advantage and difference of AIM method with other analyzing methods. In some cases, improvement in one attribute condition will give an opposite effect on other profitable attribute improvements, which is the paradox, and with "AIM" this paradox will solve.
İnşaat Sektöründe Karlılığı Artırmak İçin Yeni Bir Yaklaşım
▪ Yüksek lisans tezi.
Keywords: Couple Index (CI); Accompany Index Method (AIM); Project Attributes; Sales and Marketing; Decision Making; Project Evaluation